Test setup using DC metering approach for loss measurements of inductive components – principle, characterization, validation and application - Kohlhepp, Benedikt; Kübrich, Daniel; Peller, Stefan; Dürbaum, Thomas (Iet Power Electronics, 2021)
Accurate loss estimation of magnetic components is crucial for power electronics engineers. Unfortunately, loss predictions remain a quite challenging task, as these depend on many parameters and manufacturers typically do not deliver a sufficient database for precise loss estimations. Therefore, this paper revisits an approach allowing loss measurements. In contrast to the most common used approach using alternating current (AC) waveforms to gain information about the losses, this approach relies on measuring direct current (DC) voltage and current. After characterizing the experimental setup, air inductors serve as references to validate the approach. In a first step, the test setup is used to extract core losses with and without DC bias by designing a special device under test (DUT) featuring low winding loss. Furthermore, this paper demonstrates that the test setup is also able to gain the overall losses of complete magnetic components by using the DC metering approach.
CRIS-Team Scopus Importer:2021-06-18